Knowledge Management For Open Innovation: Collaborative Mapping Of Needs And Competencies - Paci, Augusta Maria; Lalle, Cecilia; Chiacchio, Maria Stella (Journal of Knowledge Management Practice, 2010)
In view of the European knowledge economy, a full participatory process among different units and different organizations can be established to identify solutions that meet the expectations representing high value achievements of different stakeholders’ objectives. The paper describes a reference model for a collaborative knowledge management (Co-KM) in an open innovation environment for futuring technology analysis (FTA) to support industrial innovation in the knowledge economy. This model with methods and tools allows K-community to operate more effectively and to proceed faster toward the common goal. Furthermore, it permits the mapping of community’s needs and competencies. Two experiences of Co-KM carried on inside a European project are reported.